Pemanfaatan Software Akuntansi pada Akuisisi Pengetahuan Akuntansi Mahasiswa - Yurike Rienika Chandra; Winanda Wahana Warga Dalam (Journal of Applied Accounting and Taxation, 2020)
The background of this research is to test the use of software accounting in the acquisition of student accounting knowledge. The method used in this research is laboratory experiments with instruments in the form of a questionnaire given directly to respondents after solving accounting cases manually and using software accounting. The data analysis tool used in this study was SPSS. The results of the problems examined in this study are, first, solving accounting cases manually, then solving the same cases using software accounting does not increase student accounting knowledge acquisition. The second result is that there is no significant difference in the acquisition of student accounting knowledge between the manual approach and software accounting in solving accounting cases. The last result is that there is no significant difference in acquiring accounting knowledge between male and female students in using software accounting. The conclusion and implication of this research are to be able to master and benefit from technology. In this case, accounting technology, students must understand and be familiar with using this technology. Students will be aware of the importance of technology in the world of this 4.0 industrial revolution.